1991
DOI: 10.3109/01480549109017877
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Metals with Brain Calmodulin Purified from Normal and Cadmium Exposed Rats

Abstract: Chronic exposure of cadmium (Cd) to rats (6 mg/kg body weight/day) led to a significant accumulation of Cd in brain and other organs. Calmodulin (CaM) isolated from brains of Cd exposed rats showed a decreased ability to stimulate CaM-dependent phosphodiesterase (PDE) as compared to that purified from unexposed animals. There was a dose dependent inhibition of CaM activity when CaM (from normal and Cd exposed rats) was incubated with different molar ratios of aluminium (Al3+), lead (Pb2+), manganese (Mn2+) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Cadmium was deposited in the brain and in other tissues, and caused neuronal death when injected 6 mg/kg to rats (2). It was also reported that cadmium (0.4 mg/kg) has neurotoxic effects in all regions of the brain except hippocampus when it was given into cerebra-spinal fluid of mature rats (3).…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium was deposited in the brain and in other tissues, and caused neuronal death when injected 6 mg/kg to rats (2). It was also reported that cadmium (0.4 mg/kg) has neurotoxic effects in all regions of the brain except hippocampus when it was given into cerebra-spinal fluid of mature rats (3).…”
Section: Introductionmentioning
confidence: 99%
“…Brain CaM activity was determined by measuring the stimulation of phosphodiesterase activity. A [58,61]. Lead was also found to interfere with CaM activity in vitro and in vivo.…”
Section: Disruption Of Long-term Potentiation Bymentioning
confidence: 99%
“…Calmodulin (CaM) activity is affected by aluminum, cadmium, and inorganic lead. Both aluminum and cadmium inhibited CaM activity [20,58,[60][61][62][63] whereas inorganic lead first increased CaM activity at lower concentrations (possibly by mimicking calcium), but then at higher concentrations it decreased CaM activity [59,232]. CaM is the central modulator of NMDARmediated synaptic plasticity and a majority of the regulators of synaptic plasticity depend on CaM for their activation.…”
Section: Summary Of Long-term Effectsmentioning
confidence: 99%
“…CaM bound to Cd 2+ was also detected in the brains of rats exposed to CdCl 2 . It was proposed that, since Cd 2+ has an ionic radius similar to Ca 2+ , it might interact with the Ca 2+ -binding sites on the CaM [58, 61]. …”
Section: Disruption Of Synaptic Plasticitymentioning
confidence: 99%